Common Presentation and Clinical Correlates of Celiac Disease in Pediatric Population of Pakistan - Bharo, Mumtaz Ali; Baloach, Kamran Ali Shahani; Bhanbhro, Bakhtiar Ahmed; Hamza Ishfaq; Abbas, Kiran (Pakistan Armed Forces Medical Journal, 2024)
Objective: To explore the various clinical presentations in childhood celiac disease patients of Sindh, Pakistan.Study Design: Cross-sectional studySetting and Duration of Study: Pediatric Department, Pir Abdul Qadir Shah Jeelani Institute of Medical Sciences, Gambat, Khaipur Mirs Pakistan, from Sep 2018 to Mar 2020.Methodology: A total of 140 children aged between 1-15 years, with diagnosed cases of celiac disease were enrolled in the study. Patients with inconclusive diagnosis, with multiple comorbidities, age >15 years, or children whose parents did not give consent to take part in the study were excluded from the current study. All children were further categorized according to the sociodemographic and clinical presentation.Results: The mean age of patients at the onset of symptoms was 3.15±1.25 years. Out of 140 patients, 74(52.8%) were male and 66(47.1%) female. Out of 140 patients, 28(20%) patients had positive anti-endomysial antibody titers. About 8 patients had concomitant autoimmune diseases i.e. Type 1 diabetes mellitus, out of these 5 tested positive for anti-endomysial antibody titers. The most common presentation was chronic diarrhea, seen in 13(32%) of patients.Conclusion: The current study revealed that the majority of the diagnosed pediatric patients presented with a typical clinical picture of celiac disease.